A Numerical Model for the Dynamics of Pickup Ions Outside the Heliopause and IBEX “Ribbon” Observation - Yifan Huang; Fan Guo; Eric J. Zirnstein; Sung Jun Noh; Hui Li; Daniel B. Reisenfeld; Jacob Heerikhuisen (The Astrophysical Journal)
The leading mechanism for the origin of the Interstellar Boundary Explorer (IBEX) “ribbon” of enhanced energetic neutral atoms (ENAs) from the outer heliosphere is the so-called secondary ENA process. In this mechanism, neutralized ions escape the heliosphere, and after several times of charge exchange collision,s some propagate back toward Earth in directions nearly perpendicular to the local interstellar magnetic field. However, the physical processes governing the distribution of the pickup ions (PUIs) outside the heliopause are still unclear. In this study, we build a new global model of the IBEX ribbon, where a key component is to calculate the dynamics of the PUIs outside the heliopause by solving the gyrophase-averaged focused transport equations on top of the background magnetohydrodynamic-kinetic model for the heliosphere-interstellar medium interaction. We discuss how the properties of the simulated ribbon change with different scattering parameters and show simulation results of the ENA sky maps, ribbon centers, ribbon profiles at several azimuthal slices, the ribbon ENA source region, and the velocity distribution of PUIs in the ENA source region for different scattering frequencies. Our results show that the model can provide reasonable ribbon sky maps comparable to the observed ribbon when the PUI mean free path is on the order of several thousand astronomical units.